A computational study of nanodiamond surface radicals and nitrogen-vacancy charge fluctuations. (November 2020) - Meara, Claire J.; Rayson, Mark J.; Briddon, Patrick R.; Goss, Jonathan P.
Abstract: Nanodiamonds containing negatively charged nitrogen vacancy (NV − ) centres are highly promising biolabels due to NV − photostability and spectral range. For effective cell tracking we require NV − to be stable in this charge state, but it is known that nanodiamond surfaces may alter the NV charge state; intermittent fluorescing and conversion to NV 0 are frequently observed. Different models have been proposed linking surface termination type to the resultant NV charge state, but a full understanding has not yet been reached. For the work presented in this paper, we use density functional theory to examine how the NV electronic structure in nanodiamond clusters changes with different surfaces. We move beyond examining fully terminated surfaces and focus on the role of surface radicals, based on recent research showing pH also affects NV charge. Our work shows that surface radicals can explain the intermittent fluorescence observed for hydrogenated surfaces, and that different absorbates on the surface influence the resultant NV charge for a specified termination type. We have found that both the termination type, and the absorbates on the surface, play important roles in determining NV charge and should be considered together when predicting surface coverage that will stably produce NV − . Highlights: Theoretically models the effect of surface radicals on fluorescing nanodiamonds. Examines nitrogen vacancy charge stability for different nanodiamond terminations. Shows links between absorbate properties and nitrogen vacancy charge stability.